User satisfaction in the use of available alternative formats among visually impaired users of Library for the Blind Division of the National Library - Cayabyab, Mark James G.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This research sought to find out which alternative format(Braille books, Talking books and Talking computers) available in Library for the Blind Division in The National Library is best suited for visually impaired users of the library, its perceived advantages and disadvantages by the users and the factors that influence their choice of alternative format.
The research method used for the respondents of this study is the interview. Out of 44 visually impaired users based on the LBD Members Directory that LBD provided me, only 24 were available. Data gathered from these interviews were tabulated and analyzed using the Statistical Package for Social Sciences (SPSS), using frequency and percentage distribution.
This study found out that majority of the respondents visited the library use their services only once or twice during the past 12 months. They used the services and available alternative formats whenever they have time due to work or simply because some respondents are still college and elementary students.
The main problem why respondents cannot visit and come to use LBD's services is that totally blind respondents (11) do not have someone to go with them (human guide). Nine (9) respondents say that the reason is the location and that is quite far from where they are staying or working and eight (8) respondents say that they encounter problems in transportation. But it is interesting to note that 9 out of 24 respondents say that they do not mind the challenges they meet along the way; what is important is that they go and visit the LBD and use their services
Most respondents visit LBD to use the Talking computer followed by those who borrow or use Braille books or ask the librarian to emboss a material for them in Braille form. Others go to LBD to do research, use or borrow talking books, ask the librarian to record a tape for them in cassette or head a library tour in LBD or hold meetings inside the library.
When the respondents were asked to rank the three alternative formats available in LBD according to their preference use and importance, 1 being the highest and 3 the lowest, female respondents chose to use Braille books while male respondents, on the other hand, chose Talking computers. The respondents were asked to give the LBD's overall rate when it comes to their services regarding the three available alternative formats for the visually impaired: Braille books, talking books and talking computers. Generally, the respondents gave the library "Good" rating. Gender, Age, Educational attainment, Occupation and Degree of Blindness are the factors that influence the preference and choice of alternative format of visually impaired users of LB.
Some recommendations for the improvement of the library's resources, faculties and services are offered in this paper based on the comments and suggestions of the respondents and the researcher's observation.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and people with visual disabilities; Libraries and the blind